Studi Empiris: Hubungan Antara Gaya Kepemimpinan dan Fasilitas Kerja Terhadap Kinerja Karyawan Departemen Kitchen di The Stones Hotel Legian Bali - Sudiyani, Gusti Ayu Fera Dewi; Sutapa, I Ketut; Wulandari, Pande Putu (Universitas Triatma Mulya, 2024)
This study aims to determine the effect of leadership style and work facilities on employee performance at The Stones Hotel Legian Bali. The data collection techniques used are observation, questionnaires, and interviews. The population used was kitchen department employees at The Stones Hotel Legian Bali, with a sample of 63 respondents. Based on the results of the study, it was found that leadership style has a positive and significant effect on employee performance, work facilities have a positive and significant effect on employee performance, leadership style and work facilities have an influence of 53.3% on employee performance, and work facilities variables have a more dominant influence on employee performance. Therefore, the executive chef in the kitchen department of The Stones Hotel Legian Bali is advised to be wiser in leading his subordinates, so that the work situation can be conducive. The kitchen department at The Stones Hotel Legian Bali is also expected to provide inadequate work facilities, update facilities that are no longer suitable for use, and increase the number of incentives given to employees.